DELITOS CONTRA LA PROPIEDAD A LA LUZ DEL CANON DE BENDA - Treska, Katrin (European Scientific Journal, ESJ, 2015)
Special attention should be paid to Albanian canons, as they are a testimony of our ancient legal tradition. This paper aims to analyze the crimes against property in the light of Canon of Benda. The Canon of the province of Benda, has been implemented and fully respected in the province with the same name, which included the 12 villages of Tirana. In this paper are discussed by a historical point of view the rules and provisions of the canon about the way in which this canon defended property, and sanctions provided for the crime of robbery and assault, and also the basic characteristics of these crimes.